PEMBENTUKAN DAN PELATIHAN KADER POSYANDU BALITA DI BANJAR BULUH DESA GUWANG KECAMATAN SUKAWATI KABUPATEN GIANYAR - Ni Made Wina Krisnayani; I Gede Yudiana Putra; Ni Luh Made Asri Dewi (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
Pos Pelayanan Terpadu or Posyandu are Post of Integrated Service. Posyandu were an effort to empower the community to support health development, especially in improving community health status through reducing infant mortality. Posyandu activities in Guwang Sukawati Gianyar village are one of the public health services. However, each banjar is still very minimal in terms of organizing the posyandu because the cadres do not really understand how the activities of the good posyandu. The purpose of this activity is to establish a Posyandu cadre of toddlers who are able to provide optimal health services for children under five through the implementation of a toddler posyandu. Method: Training was carried out through Community Empowering, involving 35 people who were trained as cadres. The training results are analyzed qualitatively (based on observations and results ofdiscussion). Results: Based on the evaluation in the form of pretest and posttest, it was found that there was an increase in cadre knowledge, namely from 30% to 70%. Posyandu has been conducted in 7 Banjar in the Guwang Gianyar Village. Conclusion: The establishment of skilled and trained Posyandu toddlers and able to provide optimal health services for children under five through the implementation of toddlers posyandu